Motivasi Petani Mempertahankan Lahan Pertanian Tanaman Padi Studi Kasus Kecamatan Sukoharjo Kabupaten Pringsewu - Aprildahani, Baiq Rindang; Abdiaty, Ardhea Millenia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2025)
The conversion of agricultural land into non-agricultural uses can significantly reduce the area available for food crop cultivation, posing serious risks to both local and national food security. In Sukoharjo Subdistrict, rice fields have increasingly been transformed into residential zones. Since rice is the primary staple food and a major crop cultivated by local farmers, it is essential to strengthen their motivation to preserve rice farming land. This study aims to investigate the factors that influence farmers' willingness to maintain rice cultivation in Sukoharjo. A deductive approach was employed, using quantitative methods and multiple line-ar regression analysis to identify key variables affecting farmer motivation. From the farmers’ viewpoint, several elements play a role, including age, farming experience, education level, land size, income, access to production inputs, market prices, agricultural extension services, farmer group activities, and land value. Understanding these factors is crucial for designing effective programs that support farmers in sustaining rice farming and enhancing agricultural productivity. By identifying what drives farmers to continue culti-vating rice, stakeholders can implement targeted interventions that not only protect agricultural land but also ensure long-term food supply stability in the region.